Factors Associated with Fall Risks among Older Patients of Inpatient Department in a Secondary Hospital - Buakaeo, Phongsiri; Chaichanawirote, Uraiwan; Chairat, Rungnapa (Journal of The Royal Thai Army Nurses, 2024)
The objective of this cross-sectional descriptive research was to study factors associated with fall risks among older patients in the inpatient department of a secondary hospital. The sample included 110 inpatients aged 60 years and over, recruited through purposive sampling. This method selected individuals who were conscious and able to communicate in Thai. The research tools included a record form documenting factors related to fall risks, eye health screening, the Mini Nutritional Assessment, and the Morse fall scale. The reliability of these instruments was assessed using the test-retest method, yielding stability coefficients (r) ranging from .96 to 1.0. Data analysis involved frequency statistics, percentages, means, standard deviations, Fisher’s exact probability test, and the Chi-square test. The research results revealed that a total of 85 people (77.3%) were at risk of falling. Factors significantly related to the risk of falls (p < .001) included nutritional status, urinary incontinence, vision, history of COVID-19 infection, and the group of medications received. The recommendation from this research is that nurses should pay particular attention to monitoring and preventing falls in older patients with undernutrition, urinary incontinence, vision problems, a history of COVID-19 infection, or older patients who received medications related to the Central Nervous System or Cardiovascular System.